2011
DOI: 10.1371/journal.pone.0017768
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Regeneration and Neuronal Function Are Preserved in Motor Neurons Lacking ß-Actin In Vivo

Abstract: The proper localization of ß-actin mRNA and protein is essential for growth cone guidance and axon elongation in cultured neurons. In addition, decreased levels of ß-actin mRNA and protein have been identified in the growth cones of motor neurons cultured from a mouse model of Spinal Muscular Atrophy (SMA), suggesting that ß-actin loss-of-function at growth cones or pre-synaptic nerve terminals could contribute to the pathogenesis of this disease. However, the role of ß-actin in motor neurons in vivo and its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 71 publications
3
37
0
Order By: Relevance
“…It seems likely that protein products of other axonal mRNAs also contribute to regeneration of axons. Consistent with this, mice lacking the b-actin gene apparently showed normal development and regeneration of motor axons (Cheever et al, 2011). This could indicate that b-actin is not needed for regeneration, or that other locally synthesized proteins can compensate for the loss of b-actin.…”
Section: Introductionsupporting
confidence: 54%
“…It seems likely that protein products of other axonal mRNAs also contribute to regeneration of axons. Consistent with this, mice lacking the b-actin gene apparently showed normal development and regeneration of motor axons (Cheever et al, 2011). This could indicate that b-actin is not needed for regeneration, or that other locally synthesized proteins can compensate for the loss of b-actin.…”
Section: Introductionsupporting
confidence: 54%
“…Embryos were genotyped from tail snip lysates following protocols described previously [17]. 80,000 neurons were plated in 35 mm dishes containing acid washed coverslips coated with Poly-D-Lysine (100 µg/ml) and laminin (4 µg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Also, HB9:Cre mice express the cre gene specifically in the spinal cord motor neurons and have been used previously to manipulate gene expression in the motor neurons (33). The motor neuron specificity of the HB9-driven Cre expression have also been verified by crossing the HB9:Cre mouse line to a ROSA26:LacZ reporter mice in several studies (33)(34)(35)(36)(37)(38). Examination of the GFP signals in HB9:GFP transgenic mice have indicated that expression of HB9 is restricted in the motor neurons, but not in the sensory neurons (39).…”
Section: Generation Of Mice With Conditional Knock-out Of Tardbp Exprmentioning
confidence: 99%